Jakarta's Public Perception of the Vaccine Policy Political Communication - Sinaga, Astriana Baiti; El Adawiyah, Sa'diyah (PT FORMOSA CENDEKIA GLOBAL, 2026)
This research aims to find out the public perception of government political communication related to the Minister of Health Regulation No. 10/2021: Implementation of Vaccination in the Context of Countering the Corona Pandemic 2019. Pandemic cases globally require good communication techniques from the government in disseminating information on a basis that is expected to provide a sense of security for the community in dealing with social disasters caused by the pandemic. Regulation of the Minister of Health No. 10 of 2021: The Implementation of Vaccination in the Context of the 2019 Coronavirus Pandemic has caused controversy in the community. Many opinions are developing in the community about this basic regulation of vaccination. Meanwhile, communication by the government about policies in various ways began to be felt by the public. This study uses a survey method using data collection techniques through questionnaires to find out the public's perception of government political communication related to PMK No. 10 of 2021 for a total of 424 respondents. The research was conducted in DKI Jakarta Province with the assumption that people close to the center of government should get better information (knowledge). The information bias obtained by the people of DKI Jakarta and the public rejection of this policy show that the communication is ineffective.